Synthesis and Characterization of Cellulose–Curcumin Nanofiber as a Biomaterial Mask - Novrynda Eko Satriawan; Muhamad Nasir; Fasih Bintang Ilhami (Walisongo Journal of Chemistry, 2022)
This study was conducted to characterize cellulose acetate-curcumin composite nanofibers synthesized using the electrospinning method, as a biomaterial mask with antibacterial and antiviral properties. Cellulose acetate-curcumin composite nanofibers were successfully synthesized at a flow rate of 1 mL/hour, a needle-collector distance of 17 cm, and a voltage of 22 kV. The resulted nanofibers have an average diameter in the range of 378.89 nm - 461.76 nm. Based on the results of the FTIR spectrum, no significant shift was found. The results of the contact angle test showed that the average contact angle value increased with the addition of curcumin concentration. The mechanical test results showed that variations in the concentration of curcumin were able to increase the tensile strength and strain values.